2019
DOI: 10.1016/j.neuron.2019.02.026
|View full text |Cite
|
Sign up to set email alerts
|

A Disinhibitory Microcircuit Mediates Conditioned Social Fear in the Prefrontal Cortex

Abstract: Fear behavior is under tight control of the prefrontal cortex, but the underlying microcircuit mechanism remains elusive. In particular, it is unclear how distinct subtypes of inhibitory interneurons (INs) within prefrontal cortex interact and contribute to fear expression. We employed a social fear conditioning paradigm and induced robust social fear in mice. We found that social fear is characterized by activation of dorsal medial prefrontal cortex (dmPFC) and is largely diminished by dmPFC inactivation. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(142 citation statements)
references
References 63 publications
7
133
2
Order By: Relevance
“…SST-INs not only innervate pyramidal neurons but also strongly innervate other types of INs in the cortex [33,34,46]. The increased frequency of mIPSC in PV-INs indicates an increased inhibitory input.…”
Section: Discussionmentioning
confidence: 99%
“…SST-INs not only innervate pyramidal neurons but also strongly innervate other types of INs in the cortex [33,34,46]. The increased frequency of mIPSC in PV-INs indicates an increased inhibitory input.…”
Section: Discussionmentioning
confidence: 99%
“…SOM-PV disinhibition in the thalamocortical input layer during CS+UCS pairing may allow for wider spreading of the signal from the active vibrissae in the barrel cortex. A similar disinhibitory circuit was proposed to underlie social fear in the dorsomedial prefrontal cortex, and it was shown that SOM-IN inhibition alleviates the behavioral social fear response in conditioned mice and reduces the firing rates of PV-INs, which are elevated during social fear expression (Xu et al, 2019).…”
Section: Discussionmentioning
confidence: 84%
“…to release thalamorecipient excitatory projection neurons from inhibition and enhance information flow into the upper cortical layers (Xu et al, 2013). The mechanism of disinhibition is particularly important during learning and plasticity, and the role of SOM-INs in these phenomena has been intensively investigated (Wolff et al, 2014;Xu et al, 2019). In the visual cortex, visual discrimination reduced the activity of L3 SOM-INs (Makino and Komiyama, 2015) but enhanced their stimulus selectivity, implicating them in gating selectivity changes (Khan et al, 2018).…”
Section: Som-ins Target Projection Neurons Of L4 and Fast-spiking Parmentioning
confidence: 99%
“…The ability of SFC to overcome the innate attractiveness of social interactions in small rodents was recently demonstrated by several laboratories 63,64 . Although these studies used SFC to induce general avoidance of social stimuli, we, nevertheless, developed a protocol that enables induction of avoidance behavior towards a specific individual, allowing other conspecifics to retain their attractiveness.…”
Section: Using Social Fear Conditioning For Social Discriminationmentioning
confidence: 98%